PENINGKATAN HASIL BELAJAR PESERTA DIDIK PADA PEMBELAJARAN PENDIDIKAN PANCASILA MENGGUNAKAN MODEL PROBLEM BASED LEARNING DI KELAS IV UPT SDN 03 PASAR AMPING PARAK KABUPATEN PESISIR SELATAN - Zalina, Dira; Fitria, Yanti; Putera, Rhafi Febryan; Ningsih, Yarisda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to describe the improvement of learning outcomes of Pancasila Education using the Problem Based Learning model in Class IV of UPT SDN 03 Pasar Amping Parak, Pesisir Selatan Regency. This research applies the Classroom Action Research (CAR) type using qualitative and quantitative approaches. The subjects in this research were teachers (researchers) and 20 students consisting of 10 male students and 10 female students. The results of this research indicate an increase in: a) the teaching module in cycle I obtained an average of 89.5% (SB), and in cycle II 95.85% (SB). b) the results of implementation in the teacher aspect in cycle I obtained an average of 83.9% (B), and in cycle II 92.8% (SB). c) the results of implementation in the student aspect in cycle I obtained an average of 76.8% (C), and in cycle II 96.42% (SB). d) The average learning outcomes of students in cycle I were 74.2 (C), and in cycle II it became 86.7 (B). Thus, it can be concluded that the problem-based learning model can improve student learning outcomes in Pancasila Education learning in class IV of UPT SDN 03 Pasar Amping Parak, Pesisir Selatan Regency